Association between neutrophil percentage to albumin ratio and cardiovascular disease in the metabolic syndrome population - Chengjun Li; Hongrui Lu; Haorui Chu; Wei Peng; Meiling Xu (Scientific Reports)
Abstract The association between inflammation and cardiovascular disease (CVD) is increasingly garnering attention. However, the association between neutrophil percentage to albumin ratio (NPAR) and CVD in the metabolic syndrome population remains unclear. Therefore, we employed a large-scale epidemiological database to investigate this association. Multivariable logistic regression models were used to examine the association between NPAR and CVD among people with metabolic syndrome. The potential nonlinearity was investigated by a restricted cubic spline. After detecting the nonlinearity, recursive algorithms were utilized to calculate the inflection point and effects before and after the point. Stratified analyses and interaction tests were employed to explore differences between subgroups. After adjusting for all covariates, NPAR was positively associated with CVD in the metabolic syndrome population [1.10 (1.05, 1.16)]. Subsequent analysis with restricted cubic splines revealed a nonlinear association between NPAR and CVD among adults with metabolic syndrome. A recursive algorithm identified an inflection point at 14.21. Only after this point, NPAR was positively correlated with CVD [1.12 (1.10, 1.15)]. In the subgroup analysis by sex and age, a linear association was found only in females, while others showed a nonlinear relationship. In conclusion, we observed a nonlinear relationship between NPAR and CVD in American metabolic syndrome population.